In search of security: Bulgaria’s security policy in transition - Tashev, Blagovest (Papeles del Este, 2004)
After the collapse of communism, a new strategic thinking in Bulgaria emerged only slowly. The relatively sluggish pace of the process is reflected in the late beginnings of real security and defense reform. Thus, until 1998 security sector reform was not guided by a vision and principles agreed upon by the political elite and the society at large. Political consensus on security policies emerged only in 2000. In the last several years Bulgaria’s transition has been guided by its goal of achieving membership in NATO and the European Union. The content of its foreign and security policy, too, has been guided and determined by the two Euro-Atlantic institutions. Now that membership in both organizations seems a matter of time, along with continuing the policies designed to prepare the country for accession, Bulgaria faces the challenge of formulating its security policy for the long run as a member-state. It appears that Bulgaria is going to face difficulties in formulating and applying new security policies in the framework of NATO and in the new security environment.